(untitled) (TULSSAA Journal, 2025)
In the case of COVID-19, it would be considered a global concern for managing the circumstances in an approach that will assist civilization without interfering with everyday ordinary activities, especially education for students. The author collected a hundred samples of academicians, parents, and learners across India to ascertain the importance using e-resource resources for higher education. This research methodology, which is descriptive cross-sectional, utilizes Non-Convenient Probabilistic sample as the sample technique. Open-ended as well as closed-ended inquiries concerning families as the academic community are part of the structured survey that was used to gather information about the use of e-resource learning. Frequency analysis, descriptive statistics, the Normality test (also known as the general Kolmogorov Smirnov test), the use of the U testing from Mann Whitney, key Kruskal Wallis test, or the Normality test were among the data analysis techniques used. The study discovered that, with one potential example of gender-based division, opinions regarding the usefulness of each of the three factors—"Usefulness during electronic resources learning," Each group’s demographic profile has different "The Impacts for E-Resources Learning" and "the advantages related to electronic resources learning" which has been established for the usage use E-Resources in Higher Education.